Ultrafast laser inscription: perspectives on future integrated applications. Issue 6 (2nd June 2014) - Choudhury, Debaditya; Macdonald, John R.; Kar, Ajoy K.
<x xml:space="preserve">Abstract</x> This review is focused on key emergent technologies enabled by ultrafast laser inscription (ULI). Recent progress on compact mode‐locked waveguide sources and novel mid‐infrared waveguide lasers is presented. In addition, the phenomenon and applications of selective etching in developing compact, integrated lab‐on‐chip devices are discussed. The review highlights the cross‐disciplinary potential of the ULI technology and discusses its conceivable future in impacting the aforementioned fields. <boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>